Seminar Series II for Study on Coping Strategies of Non-Chinese Students and Families in Chinese Primary Schools in Sarawak - Chai, Elena Gregoria Chin Fern; Wang, Yin Chai; Awang Ideris, Awang Daud; Ngu, Sze Song; Florianna Lendai, Michael Mulok; Siti Mariam, Abdullah; Lee, Jun Choi (2020)
The seminar was held to report on the preliminary findings based on data collection conducted in 2019. A total of 267 non-Chinese students, 164 non-Chinese parents and 91 teachers. Eight semi rural schools in Sematan, Asajaya, Sarikei and Meradong districts were visited and face to face interview were conducted. The eight schools were selected based on their significant proportion of more than 60% non-Chinese students.